2013
DOI: 10.1186/1471-2202-14-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity underlying auditory perceptual learning during short period training: simultaneous fMRI and EEG recording

Abstract: BackgroundThere is an accumulating body of evidence indicating that neuronal functional specificity to basic sensory stimulation is mutable and subject to experience. Although fMRI experiments have investigated changes in brain activity after relative to before perceptual learning, brain activity during perceptual learning has not been explored. This work investigated brain activity related to auditory frequency discrimination learning using a variational Bayesian approach for source localization, during simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 99 publications
1
11
0
1
Order By: Relevance
“…The frontal-parietal/occipital distribution of these two ICs strongly suggests a role in executive control of the processing of the input. Similar activations are widely reported during basic auditory processing tasks (e.g., Anderson, Ferguson, Lopez-Larson, & Yurgelun-Todd, 2010; de Souza, Yehia, Sato, & Callan, 2013; Henry, Herrmann, & Obleser, in press; Sabri, Humphries, Binder, & Liebenthal, 2008; Shaywitz, Shaywitz, Pugh, Fulbright, Skudlarski, Mencl, & Gore, 2001; Sturm et al, 2011) and these effects are typically bilateral. In the present study, bilateral activation was seen, but it was segregated across two independent components, which showed left and right hemisphere lateralization respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The frontal-parietal/occipital distribution of these two ICs strongly suggests a role in executive control of the processing of the input. Similar activations are widely reported during basic auditory processing tasks (e.g., Anderson, Ferguson, Lopez-Larson, & Yurgelun-Todd, 2010; de Souza, Yehia, Sato, & Callan, 2013; Henry, Herrmann, & Obleser, in press; Sabri, Humphries, Binder, & Liebenthal, 2008; Shaywitz, Shaywitz, Pugh, Fulbright, Skudlarski, Mencl, & Gore, 2001; Sturm et al, 2011) and these effects are typically bilateral. In the present study, bilateral activation was seen, but it was segregated across two independent components, which showed left and right hemisphere lateralization respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Left lateralized activations, similar to that in IC-2, have also been reported for improvements in processing of nonspeech sound contrasts (de Souza et al, 2013) and under conditions that vary attentional load for processing non-meaningful consonant-vowel stimuli (Westerhousen, Moosmann, Alho, Belsby, Hämäläinen, Medvedev, & Hugdahl, 2010). For this reason, we suggest that IC-2 may have reflected attention to short-duration acoustic information in the speech stream.…”
Section: Discussionmentioning
confidence: 62%
“…Most of these studies on perceptual learning in psychoacoustic measures have tested long-term learning, going on for several days. Only a few tested short-term learning but nonetheless reported on training effect [41,44,45]. Moreover, Cohen et al [44] suggested that shorter training sessions facilitate more latent learning.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, most researches on auditory learning extend their experiments for several days (e.g. Cuddy, 1970;Menning et al, 2000;Foxton & Brown, 2004;Russo et al, 2005;Seppanen et al, 2012;Paraskevopoulos et al, 2012), although neural plasticity has been documented to take place rapidly, even after a single training session with auditory and visual (Souza et al, 2013) and audiovisual stimulation (Zilber et al, 2014). In this context, it is noteworthy that our results emerged from a very short training protocol: approximately 55 min.…”
Section: Behavioral Improvementmentioning
confidence: 55%